A dominant negative form of the transcription factor c-Jun affects genes that have opposing effects on lipid homeostasis in mice - Drosatos, K.; Sanoudou, D.; Kypreos, K. E.; Kardassis, D.; Zannis, V. I. (J Biol ChemJ Biol ChemJ Biol Chem, 2007)
c-Jun is a transcription factor activated by phosphorylation by the stress-activated protein kinase/c-Jun N-terminal kinase pathway in response to extracellular signals and cytokines. We show that adenovirus-mediated gene transfer of the dominant negative form of c-Jun (dn-c-Jun) in C57BL/6 mice increased greatly apoE hepatic mRNA and plasma levels, increased plasma cholesterol, triglyceride, and very low density lipoprotein levels, and resulted in the accumulation of discoidal high density lipoprotein particles. A similar but more severe phenotype was generated by overexpression of the mouse apoE in C57BL/6 mice, suggesting that dyslipidemia induced by dn-c-Jun was the result of apoE overexpression. Unexpectedly, infection of apoE(-/-) mice with adenovirus expressing dn-c-Jun reduced plasma cholesterol by 70%, suggesting that dn-c-Jun affected other genes that control plasma cholesterol levels. To identify these genes, we performed whole genome expression analysis (34,000 genes) of isolated livers from two groups of five apoE(-/-) mice, infected with adenoviruses expressing either the dn-c-Jun or the green fluorescence protein. Bioinformatic analysis and Northern blotting validation revealed that dn-c-Jun increased 40-fold the apoE mRNA and reduced by 70% the Scd-1 (stearoyl-CoA-desaturase 1) mRNA. The involvement of Scd-1 in lowering plasma cholesterol was confirmed by restoration of high cholesterol levels of apoE(-/-) mice following coinfection with adenoviruses expressing dn-c-Jun and Scd-1. In conclusion, dn-c-Jun appears to trigger two opposing events in mice that affect plasma cholesterol and triglyceride levels as follows: one results in apoE overexpression and triggers dyslipidemia and the other results in inhibition of Scd-1 and offsets dyslipidemia.
Drosatos, KonstantinosSanoudou, DespinaKypreos, Kyriakos EKardassis, DimitrisZannis, Vassilis IengR01 HL048739-11/HL/NHLBI NIH HHS/HL48739/HL/NHLBI NIH HHS/R01 HL048739/HL/NHLBI NIH HHS/R01 HL033952/HL/NHLBI NIH HHS/R01 HL068216/HL/NHLBI NIH HHS/R01 HL068216-05A1/HL/NHLBI NIH HHS/HL33952/HL/NHLBI NIH HHS/Research Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov't2007/04/26 09:00J Biol Chem. 2007 Jul 6;282(27):19556-64. doi: 10.1074/jbc.M700986200. Epub 2007 Apr 24.
Keywords: *Genes, Dominant; *Homeostasis/genetics; *Lipid Metabolism/genetics; *Signal Transduction/genetics; Adenoviridae; Animals; Apolipoproteins E/biosynthesis/deficiency; Cell Line, Tumor; Cholesterol/blood; Dyslipidemias/blood/genetics; Genome; Humans; JNK Mitogen-Activated Protein Kinases/genetics/metabolism; Liver/metabolism; Mice; Mice, Knockout; Proto-Oncogene Proteins c-jun/*biosynthesis/genetics; RNA, Messenger/biosynthesis/genetics; Stearoyl-CoA Desaturase/genetics/metabolism; Triglycerides/blood